2015
DOI: 10.3389/fpsyg.2015.00900
|View full text |Cite
|
Sign up to set email alerts
|

The influence of stereotype threat on immigrants: review and meta-analysis

Abstract: In many regions around the world students with certain immigrant backgrounds underachieve in educational settings. This paper provides a review and meta-analysis on one potential source of the immigrant achievement gap: stereotype threat, a situational predicament that may prevent students to perform up to their full abilities. A meta-analysis of 19 experiments suggests an overall mean effect size of 0.63 (random effects model) in support of stereotype threat theory. The results are complemented by moderator a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 77 publications
3
72
0
2
Order By: Relevance
“…First, our study expands previous stereotype threat literature (e.g., Appel, Weber, & Kronberger, 2015;Martiny & Götz, 2011;Nguyen & Ryan, 2008) by showing that vertical collectivism can influence stereotype threat effects. This interaction effect might help explain the heterogeneous effect sizes of stereotype threat effects reported in meta-analyses (e.g., Nguyen & Ryan, 2008).…”
Section: Effects On Performancesupporting
confidence: 54%
See 1 more Smart Citation
“…First, our study expands previous stereotype threat literature (e.g., Appel, Weber, & Kronberger, 2015;Martiny & Götz, 2011;Nguyen & Ryan, 2008) by showing that vertical collectivism can influence stereotype threat effects. This interaction effect might help explain the heterogeneous effect sizes of stereotype threat effects reported in meta-analyses (e.g., Nguyen & Ryan, 2008).…”
Section: Effects On Performancesupporting
confidence: 54%
“…We contribute to the existing research literature on stereotype threat effects for migrants (e.g., Appel et al, 2015;Froehlich, Martiny, Deaux, Goetz, et al, 2016;Martiny et al, 2015) by revealing that vertical collectivism interacts with the activation of negatives stereotypes on performance and individual mobility motivation. Our findings are also relevant to work on the relationship between individual differences in student characteristics and achievement-related outcomes (e.g., Jurik et al, 2014) revealing that migrant students with high vertical collectivism endorsement suffer from stereotype threat effects.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the well-established stereotype threat effects for African-Americans (e.g., Brown & Day, 2006;Steele & Aronson, 1995), relatively little work has investigated stereotype threat effects for immigrants (Appel, Weber, & Kronberger, 2015). One exception is Deaux et al (2007), who investigated stereotype threat for West Indian immigrants in the United States.…”
Section: Stereotype Threat For Immigrants In Europementioning
confidence: 97%
“…However, individuals with a migration background also showed lower test performance in nonverbal intelligence. Existing literature suggests that not only language barriers but also cultural and environmental differences such as familiarity with tasks used in intelligence tests [11, 12], stereotype threat [13, 18], and parental language skills [14] can contribute to lower test performance in individuals with a migration background [10], which also might have led to the lower test scores of individuals with a migration background in the verbal and nonverbal intelligence indexes in the present study. In sum, the results of the present study indicate that using the German version of the RIAS may lead to underestimated intelligence test scores in individuals with a migration background.…”
Section: Discussionmentioning
confidence: 85%
“…For example, individuals with a migration background may be less familiar with the type of tasks used in performance assessment [11, 12]. In addition, many immigrant groups are confronted with negative achievement stereotypes, which may create increased performance pressure [13]. Furthermore, studies have shown that immigrant children’s parents who have limited language skills in the dominant language are less involved in schooling, which in turn may negatively affect their children’s performance [14, 15].…”
Section: Introductionmentioning
confidence: 99%